A numerical algorithm for filtering and state observation - Ibrir, Salim (Zielona Góra: Uniwersytet Zielonogórski)
This paper deals with a numerical method for data fitting and estimation of continuous higher-order derivatives of a given signal from its non-exact sampled data. The proposed algorithm is a generalization of the algorithm proposed by Reinsch (1967). This algorithm is conceived as a key element in the structure of the numerical observer discussed in our recent papers. Satisfactory results are obtained which prove the efficiency of the proposed approach.
Keywords: spline functions; numerical differentiation; observers; smooth filters